1982
DOI: 10.1182/blood.v60.4.834.bloodjournal604834
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of human platelet membrane microparticles from plasma and serum

Abstract: Methods have been developed to isolate human platelet membrane fragments from plasma and serum. Rabbit antibody produced against the human platelet membrane glycoprotein complex, IIb/IIIa, was utilized in an immunoelectrophoretic assay to evaluate the amount of this antigen in various microparticle preparations. The serum concentration of platelet microparticles was more than tenfold greater than that observed for plasma (65 micrograms/ml versus 4.4 micrograms/ml, respectively). Ultrastructural evaluation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 0 publications
1
66
0
1
Order By: Relevance
“…PC supernatant, all from the same PC, collected after one or two centrifugation runs showed background reaction with long R‐times of 23 and 46 minutes and low MA values of 32 and 8 mm, respectively. Because it is known that a much higher g value and/or dilution is needed to isolate microparticles from plasma, it was concluded that PC supernatant still contained PLT membrane microparticles or phospholipids and thus could not be used as diluent because of this background reactivity. PL‐UC showed reaction with kaolin but no reaction at all with collagen during more than 60 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…PC supernatant, all from the same PC, collected after one or two centrifugation runs showed background reaction with long R‐times of 23 and 46 minutes and low MA values of 32 and 8 mm, respectively. Because it is known that a much higher g value and/or dilution is needed to isolate microparticles from plasma, it was concluded that PC supernatant still contained PLT membrane microparticles or phospholipids and thus could not be used as diluent because of this background reactivity. PL‐UC showed reaction with kaolin but no reaction at all with collagen during more than 60 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…George et al (1982, 1986) were the first to isolate PDMP from stored fresh frozen plasma and platelet concentrates Bode et al (1991) quantified microparticles in platelet concentrates during storage using flow cytometry and demonstrated that MP numbers significantly increased with time. These authors further showed that the majority of MP in platelet concentrates were of platelet origin.…”
mentioning
confidence: 99%
“…It was hypothesized that these EVs may be involved in the self-renewal and expansion of pluripotent or multipotent stem cells in vitro, and Ratajczak et al (138) demonstrated that embryonic stem cell-derived EVs were able to induce changes in hematopoietic progenitor cells (138). In particular, these vesicles were shown to contain Wnt-3, a factor involved in stem cell expansion (63,70,74), and they were also enriched in the pluripotent stem cell transcription factor Oct-4. In addition, RNAse treatment showed that EVs contained not only the protein Oct-4 but also its mRNA, which can be translated within the target cells (138).…”
Section: Stem Cell Niche and Evsmentioning
confidence: 99%